Progress and prospects in stem cell therapy - Xu Xiu-ling; Yi Fei; Pan Hui-ze; Duan Shun-lei; Ding Zhi-chao; Yuan Guo-hong; Qu Jing; Zhang Hai-chen; Liu Guang-hui (Acta Pharmacologica Sinica, 2016)
Xiu-ling XU1, #, *, Fei YI2, #, Hui-ze PAN1, Shun-lei DUAN1, Zhi-chao DING1, Guo-hong YUAN1, Jing QU1, Hai-chen ZHANG1, Guang-hui LIU1, * 1National Laboratory of Biomacromolecules, Institute of Biophysics, Chinese Academy of Sciences, Beijing 100101, China; 2Department of Molecular and Cellular Physiology, Stanford University School of Medicine, 265 Campus Drive, Stanford, CA 94305, USA In the past few years, progress being made in stem cell studies has incontestably led to the hope of developing cell replacement based therapy for diseases deficient in effective treatment by conventional ways. The induced pluripotent stem cells (iPSCs) are of great interest of cell therapy research because of their unrestricted self-renewal and differentiation potentials. Proof of principle studies have successfully demonstrated that iPSCs technology would substantially benefit clinical studies in various areas, including neurological disorders, hematologic diseases, cardiac diseases, liver diseases and etc. On top of this, latest advances of gene editing technologies have vigorously endorsed the possibility of obtaining disease-free autologous cells from patient specific iPSCs. Here in this review, we summarize current progress of stem cell therapy research with special enthusiasm in iPSCs studies. In addition, we compare current gene editing technologies and discuss their potential implications in clinic application in the future. Keywords: induced pluripotent stem cells (iPSCs); stem cell therapy; gene editing; neurological disorders; hematologic diseases; cardiac diseases; liver diseases Guang-hui LIU is supported by the Strategic Priority Research Program of the Chinese Academy of Sciences (XDA01020312), the National Natural Science Foundation of China (NSFC) (81271266, 31222039), the Thousand Young Talents program of China, the National Laboratory of Biomacromolecules (013kf05, 2013kf11), and State Key Laboratory of Drug Research (SIMM1302KF-17). Xiu-ling XU is supported by NSFC (31201111). # These authors contributed equally to this paper. * To whom correspondence should be addressed. E-mail ghliu@ibp.ac.cn (Guang-hui LIU); xiulingxu@hotmail.com (Xiu-ling XU) Received 2013-03-19 Accepted 2013-05-16